1998
DOI: 10.1128/jb.180.17.4452-4459.1998
|View full text |Cite
|
Sign up to set email alerts
|

Biochemistry and Regulation of a Novel Escherichia coli K-12 Porin Protein, OmpG, Which Produces Unusually Large Channels

Abstract: A novel porin, OmpG, is produced in response to a chromosomal mutation termed cog-192. Molecular characterization ofcog-192 revealed that it is a large chromosomal deletion extending from the 3′ end of pspA through to the 5′ end of an open reading frame located immediately upstream of ompG. As a result of this 13.1-kb deletion, the expression ofompG was placed under the control of the pspApromoter. Characterization of OmpG revealed that it is quite different from other porins. Proteoliposome swelling assays sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 41 publications
3
76
0
1
Order By: Relevance
“…Hence, the mechanism of activation of mspB and mspD transcription remains obscure. These results show that the mspB and mspD genes function as backup porins in M. smegmatis similar to several silent porin genes of E. coli (Highton et al, 1985;Blasband et al, 1986;Fajardo et al, 1998;Prilipov et al, 1998). These results indicate further that: (i) deletion of mspA may be detrimental for M. smegmatis unless expression of other porin genes compensates for the loss of MspA and (ii) the permeability defects of the mspA mutants are alleviated by additional expression of other porin genes and underestimate the real physiological role of MspA in wild-type M. smegmatis.…”
Section: Discussionmentioning
confidence: 54%
“…Hence, the mechanism of activation of mspB and mspD transcription remains obscure. These results show that the mspB and mspD genes function as backup porins in M. smegmatis similar to several silent porin genes of E. coli (Highton et al, 1985;Blasband et al, 1986;Fajardo et al, 1998;Prilipov et al, 1998). These results indicate further that: (i) deletion of mspA may be detrimental for M. smegmatis unless expression of other porin genes compensates for the loss of MspA and (ii) the permeability defects of the mspA mutants are alleviated by additional expression of other porin genes and underestimate the real physiological role of MspA in wild-type M. smegmatis.…”
Section: Discussionmentioning
confidence: 54%
“…Projection maps at 6 Å resolution obtained by electron cryo-microscopy of two different two-dimensional (2D) crystal forms revealed a ring-shaped density indicative of a monomeric b-barrel, with no evidence of oligomer formation. Initial secondary structure predictions of OmpG suggested 16 b-strands (Fajardo et al, 1998), but more recent estimates (Conlan et al, 2000;Behlau et al, 2001) put this number at 14, which agrees better with the diameter of the b-barrel in the projection maps.…”
Section: Introductionmentioning
confidence: 56%
“…Chemical crosslinking and two-dimensional electrophoresis suggested that OmpG is a monomer (Fajardo et al, 1998), unlike the classical outer-membrane porins which are trimers (Nikaido, 2003). Projection maps at 6 Å resolution obtained by electron cryo-microscopy of two different two-dimensional (2D) crystal forms revealed a ring-shaped density indicative of a monomeric b-barrel, with no evidence of oligomer formation.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations